PENGOBATAN TRADISIONAL BADAH AYAM DI NAGARI LUBUK BASUNG SUMATERA BARAT - Yoza, Alifa Kamila; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Traditional medicine badah ayam is a non-medical treatment or alternative medicine for the Minang people who use chicken as a medium for treatment. This research was conducted in Nagari Lubuk Basung, West Sumatra. The purpose of this research is to find out the process of implementing traditional medicine badah ayam and the reasons why people still use and trust this treatment. In this study the technique of taking the subject by using snow ball and purposive sampling which criteria have been determined in this study. The theory used in this study uses the theory of social action (traditional action and value rationality) put forward by Max Weber and health belief model theory. This research uses a qualitative approach with a descriptive type. To obtain relevant research results, researchers conducted interviews with 8 subjects and also made direct observations in the field. The results of this study are that there are procedures for carrying out treatment and the reasons people use and trust this treatment. This traditional medicine uses chicken as a medium in which the disease in the patient's body is transferred to the chicken and you can see the disease suffered, then the chicken is consumed by the patient along with the spice leaves given by the person treating it. The reason people use this treatment is because of family traditions, treatment is more effective than medical treatment, diseases that do not go away. The reason people believe in this treatment is because this treatment has existed since ancient times and has survived to this day, family habits, and also the results and effects provided by traditional medicine to install badah ayam. Keywords: Treatment of Badah Ayam, Social Action Theory, Lubuk Basung